Drug prescriptions in Danish out-of-hours primary care: a 1-yearpopulation-based study. (1st October 2016) - Christensen, Morten Bondo; Nørøxe, Karen Busk; Moth, Grete; Vedsted, Peter; Huibers, Linda
Abstract: Objective: General practitioners are the first point of contact in Danish out-of-hours (OOH) primary care. The large number of contacts implies that prescribing behaviour may have considerable impact on health-care expenditures and quality of care. The aim of this study was to examine the prevailing practices for medication prescription in Danish OOH with a particular focus on patient characteristics and contact type. Design and setting: A one-year population-based retrospective observational study was performed of all contacts to OOH primary care in the Central Denmark Region using registry data. Main outcome measures: Prescriptions were categorised according to Anatomical Therapeutic Chemical Classification (ATC) codes and stratified for patient age, gender and contact type (telephone consultation, clinic consultation or home visit). Prescription rates were calculated as number of prescriptions per 100 contacts. Results: Of 644, 777 contacts, 154, 668 (24.0%) involved medication prescriptions; 21.9% of telephone consultations, 32.9% of clinic consultations and 14.3% of home visits. Around 53% of all drug prescriptions were made in telephone consultations. Anti-infective medications for systemic use accounted for 45.5% of all prescriptions and were the most frequently prescribed drug group for all contact types, although accounting for less than 1/3 of telephone prescriptions. Other frequently prescribed drugs were ophthalmological anti-infectives (10.5%), NSAIDs (6.4%), opioids (3.9%), adrenergic inhalants (3.0%) and antihistamines (2.3%). Conclusion: About 25% of all OOH contacts involved one or more medication prescriptions. The highest prescription rate was found for clinic consultations, but more than half of all prescriptions were made by telephone. KEY POINTS: As the out-of-hours (OOH) primary care services cover more than 75% of all hours during a normal week, insight into the extent and type of OOH drug prescription is important. General practitioners (GPs) are responsible for more than 80% of all drug prescriptions in Denmark. Of all contacts 24.0% involved medication prescriptions; 21.9% of telephone consultations, 32.9% of clinic consultations and 14.3% of home visits. Of all prescriptions, 53% were made in telephone consultations. Anti-infective medications for systemic use accounted for 45.5% of all prescriptions, thereby being the most frequently prescribed drug group for all three contact types.